Posthumanist Shakespeares - Herbrechter, Stefan (Palgrave Macmillan, 2012)
Shakespeare scholars and cultural theorists critically investigate the relationship between early modern culture and contemporary political and technological changes concerning the idea of the 'human.' The volume covers the tragedies King Lear and Hamlet in particular, but also provides posthumanist readings of other Shakespearean plays
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Posthumanismus; Shakespeare, William